Sound Design dan Representasi Identitas Musikal : Analisis Teknis dan Persepsi Audiens pada Lagu “Panjang Umur Pekerja Keras” Karya Dhyo Haw - Muhamad Rizqy Nur Ardian; Mochammad Usman Wafa (Jurnal Riset Rumpun Seni, Desain dan Media, 2025)
This study aims to determine and analyze the influence of product development, service quality, and pricing on sales volume at PT Indoqurma Sejahtera, East Jakarta. The background of this study is based on increasingly fierce business competition, especially in the trading industry, so companies need to identify factors that influence sales volume. This study uses a quantitative approach with data collection techniques through distributing questionnaires to 50 employees directly involved in marketing and sales activities, using a saturated sampling technique. The research instrument was tested for validity and reliability before use. Data analysis was carried out using multiple linear regression using SPSS software version 19, which includes the classical assumption test, t-test, F-test, and coefficient of determination. The results show that the variables of product development and service quality do not have a significant influence on sales volume. This indicates that the company's product development efforts have not been fully able to increase market appeal or have not been in accordance with consumer needs. Similarly, the implemented improvements in service quality have not had a significant impact on increasing sales volume. In contrast, pricing has been shown to have a significant influence on sales volume. These findings indicate that consumers in PT Indoqurma Sejahtera's target market are highly price-sensitive, thus a competitive pricing strategy can be a key factor in driving sales. Based on these results, managerial implications include the need to reevaluate product development strategies and improve service quality to be more relevant to consumer needs and preferences.